Using nanocomposite hydrogel with N-urea in substrates for production of pepper seedlings (Bioagro, 2020)
Sweet pepper is one of the vegetables of greater economic importance worldwide, and also in Brazil. In its cultivation, the production of quality seedlings is essential for the obtainment of vigorous and productive plants. The technique of adding hydrogels as water-conditioners and nutrient carriers has been used for this purpose with promising results. The objective of this work was to evaluate the use of a nanocomposite hydrogel with controlled release properties of N-urea in the production of pepper seedlings. The trial was established in experimental design of randomized blocks with five treatments and four replicates. The treatments consisted of the use of 6 g∙L-1 of the polymer, with pure hydrogel (HP) and proportions of nanocomposite hydrogel incorporated with N-urea (HU), which were added to the substrate in concentrations of 0, 5, 10, 15 and 40 %. The highest concentrations presented beneficial effects on the quality of the seedlings, in variables such as plant height, leaf area, stem diameter and Dickson quality index, with prominence for the doses of 40 % HU.
Keywords: Capsicum annuum; nitrogen fertilizer; polymer; vegetables